Efficacy of probiotics administration in prevention of migraine in children: A randomized clinical trial study. : probiotics administration in prevention of migraine in children - bazmamoun, hassan; Fayyazi , Afshin; Keshtkar Sohi , Bentolhoda; Mohammadi , Younes (Iranian Journal of Child Neurology, 2024)
Objectives Migraine is a chronic and joint disease in children. The results of previous studies on the effectiveness of probiotics in preventing migraine attacks in children have been controversial. This study aims to investigate the effect of probiotics on migraine prophylaxis in children. Materials & Methods In this clinical trial study, 41 children aged 5 to 15 with migraine enrolled the study in two control and intervention groups. Children in the intervention group (18 children) received propranolol at a dose of 1 mg per kilogram of body weight daily in two divided doses along with a 250 mg Yomogi capsule daily for three months, and children in the control group (23 children), received propranolol along with placebo for three months. The study compared the frequency and duration of headache days, PedMIDAS criteria, and parental satisfaction between the two groups before treatment, as well as one month and three months post-treatment. Results The number of headache days in both groups decreased over time, but in the intervention group, this decrease was more than the control group was statistically significant (P=0.045). The average PedMIDAS scale after treatment in the intervention group was 3.9 ± 3.8; in the control group, it was 8.4 ± 8.2, which was statistically significant (P=0.047). Parents’ satisfaction with the treatment was statistically significantly higher in the intervention group (94.4%) than in the control group (54.5%) (P=0.011). No significant drug complications were seen in any of the two groups. Conclusion In children with migraine, adding probiotics to migraine treatment reduces the intensity and number of days of children’s headaches and increases the Parents’ satisfaction with the treatment